Kinetics for dislocation structure formation in contact area of squeezed crystalline solids - Boyko, Yu.I.; Volosyuk, M.A.; Kononenko, V.G. (Functional Materials, 2013)
Evolution of dislocation structure during formation of the contact area was studied in modeling experiments "wedge-plane" for KCl single crystal under loading at room and high (0.8Tm) temperatures. It was shown that at the first (rapid) stage of the process, a quasi-stationary dislocation assemblage is formed due to emission of dislocations. It was established that at high temperature (0.8Tm), the cellar structure (CS) was formed at the earliest stages of annealing under loading. The experimentally determined dislocation critical density ρ c at which the CS is formed ρ c≈ 10⁷ cm⁻² is by the order of value corresponds to the calculated one (10⁶< ρc< 10¹⁰) cm⁻². The crystal-likeness of the CS predicted by the theory is supported qualitatively; the CS contains a mixture of cells-polygons with the number of sides predominantly from 4 to 6.